TINDAK TUTUR ILOKUSI BERTANYA GURU - Eka Nurul Mualimah (Universitas Setia Budhi Rangkasbitung, 2018)
The speech act asked in the process of learning Indonesian at Wadasari Elementary School was chosen as the object of research because the speech act asked was the d ominant speech act in the learning process. The purpose of this study was to describe the form of illocutionary speech acts asking the function of speech acts to ask in the Indonesian language learning process. This study uses qualitative research methods with a type of ethnographic micro case study research. The data in this study were collected by observation, recording and interview techniques. The results showed that the form of speech acts asked in the process of learning Indonesian language at Wadasari Elementary School was a literal direct speech act. The illocutionary form that appears in the speech act to ask the teacher is directive, assertive and expressive.